On Farm Testing of Rice Residue Management Techniques for Wheat (Triticum aestivum L.) Establishment in Punjab - Gupta, Alok; Singh, Pritpal; Singh, Gurdeep; Sekhon, Bhallan Singh; Sodhi, Gurjinder Pal Singh (Indian Journal of Extension Education, 2021)
Rice residue management (RRM) has been the key component of systems’ sustainability. The paper reports the effect of different RRM and wheat (Triticum aestivum L.) establishment methods on productivity and yield contributing attributes through farmer participatory mode in south-western Punjab. Different RRM technologies including rice residue removal, residue incorporation and residue retention on soil as surface mulch were evaluated. Wheat grain yield was significantly (p
Keywords: Residue incorporation; Residue removal; Residue retention; Wheat establishment; Economic indices